THE EFFECT OF hCG (Human Chorionic Gonadotropin) INJECTION WITH DIFFERENT DOSAGE ON OVULATION AND EGGS QUALITY OF DOKUN (Barbodes lateristriga) - Qory Aulia Zukrina; Nuraini Nuraini; Sukendi Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTThis research was conducted from March to August 2020 at the Laboratory of Fish Hatchery and Breeding at the Faculty of Fisheries and Marine Sciences, University of Riau.This study aims to determine the effect of hCG injection with different doses on the ovulation of Dokun Fish (Barbodes lateristriga) and to determine the right dose of hCG to produce quality Dokun Fish eggs (Barbodes lateristriga).The treatment in this study was D0: injection of 0.9% NaCl as control fish, D350: injection of hCG at a dose of 350 IU / kg body weight, D450: injection of hCG at a dose of 450 IU / kg body weight, D550: injection of hCG at a dose of 550 IU / kg body weight.The results of this study indicate that the hCG dose of 450 IU / kg body weight is the best with a latency time of 6 hours 6 minutes, the number of eggs from stripping 45 eggs / g of the female parent, an increase in egg diameter of 0.06 mm, an increase in egg maturity of 25.56%, the value of the ovisomatic index (IOS) was 6.32%. Measurements of water quality during the study were temperature of 27-290C, pH 5-6, and DO from 5.2 to 5.6 ppm.Keywords: hCG, Ovulationi, Eggs Quality, Barbodes lateristriga